International Paper : Drawings by Emerging Artists. - Elaine, James; Isé, Claudine; Philbin, Ann; UCLA Hammer Museum, Los Angeles (Los Angeles : UCLA Hammer Museum, 2003)
Bachhuber, Nina Lola ; Bleecker, Hillary ; Brown, Iona Rozeal ; Castaño, Carolyn ; Takeshi, Honda ; Könitz, Alice ; Lansing-Dreiden ; Li Jin ; Lowe, Nick ; Masnyj, Yuri ; McCarty, Kim ; Morse, Aaron ; Mukherjee, Sandeep ; Nordström, Jockum ; O'Dell, Shaun ; Pessoli, Alessanro ; Sawaguchi, Shunsuke ; Schatz, Silke ; Sontheimer, Matthew ; Van Tran, Tam ; Vargas-Lugo, Pablo ; Wulff, Katharina
International Paper : Drawings by Emerging Artists, UCLA Hammer Museum, Los Angeles, 26 January - 27 April 2003
boek